A combination of green tea, rhodiola, magnesium and B vitamins modulates brain activity and protects against the effects of induced social stress in healthy volunteers. (2nd September 2022) - Boyle, Neil Bernard; Billington, Jac; Lawton, Clare; Quadt, Frits; Dye, Louise
ABSTRACT: Background: Magnesium (Mg), green tea and rhodiola extracts have, in isolation, been shown to possess stress and anxiety relieving effects. Green tea and rhodiola have been shown to modulate EEG oscillatory brain activity associated with relaxation and stress perception. The combined capacity of these ingredients to confer protective effects under conditions of acute stress has yet to be examined. We tested the hypothesis that a combination of Mg (with B vitamins) + green tea + rhodiola would acutely moderate the effects of stress exposure. Methods: A double blind, randomised, placebo controlled, parallel group design was employed (Clinicaltrials.gov:NCT03262376; 25/0817). One hundred moderately stressed adults received oral supplementation of either (i) Mg + B vitamins + green tea + rhodiola; (ii) Mg + B vitamins + rhodiola; (iii) Mg + B vitamins + green tea; or (iv) placebo. After supplementation participants were exposed to the Trier Social Stress Test. The effects of the study treatments on electroencephalogram (EEG) resting state alpha and theta, subjective state/mood, blood pressure, heart rate variability and salivary cortisol responses after acute stress exposure were assessed. Results: The combined treatment significantly increased EEG resting state theta ( p < .02) – considered indicative of a relaxed, alert state, attenuated subjective stress, anxiety and mood disturbance, and heightened subjective and autonomic arousal ( p < .05). Conclusions: Mg, B vitamins, rhodiola and green tea extracts are a promising combination of ingredients that may enhance coping capacity and offer protection from the negative effects of stress exposure. Trial registration : ClinicalTrials.gov identifier: NCT03262376 .